Quality of life among alcohol-dependent patients: How satisfactory are the available instruments? A systematic review - Luquiens, A.; Reynaud, M.; Falissard, B.; Aubin, H.J. (Drug and alcohol dependence, 2012)
The purpose of this systematic review was to compare quality-of-life instruments used as outcome measures in randomized clinical trials for alcohol-dependence treatment. Randomized controlled clinical trials, indexed in the EMBASE, PubMed and PsycINFO databases since 1981, which aimed at improving the quality of life in alcohol-dependent patients and used as instrument to measure the quality of life, as specifically designated by the authors, were included. Of the 331 articles screened, 18 studies were included in the review. Eight different quality-of-life instruments were used as outcome measures. Twenty-seven life domains were explored. Between-scale heterogeneity was high. The scale most frequently used was the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36). Only 1 clinical trial demonstrated a significant difference between intervention groups at all endpoints, using the Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q). Because many different instruments were used, it is difficult to compare quality-of-life improvement between trials. The most frequently used instrument was a generic health status measure that may not be well suited as a quality-of-life measure for subjects with alcohol dependence. The construction and validation of a specific patient-reported outcome based on alcohol-dependent patients’ concerns would effectively contribute to the assessment of treatment efficacy.